Investigation of the Effects of Acupuncture on Post-Operative Chest Pain after Open Heart Surgery - Sharareh Roshanzamir; Yas Haririan; Rezvan Ghaderpanah; Leila Sadat Mohamadi Jahromi; Alireza Dabbaghmanesh (Medical Association of Pharmacopuncture Institute, 2023)
Background : Coronary artery bypass grafting (CABG) accounts for more than half of all adult cardiac surgeries worldwide. Post-operative chest pain is a common CABG complication and can cause significant discomfort. Objectives: Because taking large amounts of analgesics can have many side effects, we evaluated whether acupuncture effectively reduces pain and the use of analgesics by CABG patients. Methods : In this clinical trial, 30 patients who had recently undergone CABG were randomly allocated to two groups. For both groups, exercise therapy and routine analgesics were recommended. The intervention group underwent bilateral acupuncture in distinct acupoints, including the HT3, HT4, HT5, HT6, HT7, PC3, PC5, PC6, and PC7 for 10 daily sessions constantly. Visual analog scale (VAS) and analgesic use were evaluated in both groups at baseline and after completing the 10-day treatment. Results : Our analysis revealed significant decreases in the mean VAS scores in both the intervention and the control group, and that the reduction was more significant in the acupuncture group (p < 0.001). Moreover, analgesic use was significantly lower in the acupuncture group when compared with the control group (p < 0.001). Conclusion : Our findings highlight acupuncture as an alternative method of controlling CABG-associated post-operative chest pain and reducing the use of analgesics, which might have many side effects.